Gas and grain : the conservation of networked industrial landscapes - Worth, David (Department of Archaeology, 2018)
This thesis examines the networked industrial landscapes of Cape Town's nineteenth century gas supply industry, and South Africa's twentieth century grain elevator system. The thesis takes the view that, although created in very differing circumstances, both networks were explicitly constructed with the purpose of social and economic development, albeit for narrowly defined constituencies. In both cases, important component sites of these networks came to the end of their working lives during the course of this research. The Woodstock gas works has since been demolished, and the Cape Town grain elevator stands derelict. The principle question of this thesis asks whether the networks of which these sites formed an integral part, can be conserved with the purpose of future social and economic development within the broad framework of Agenda 21. Working within a methodological framework informed by the Kerr's Conservation Plan work, research was conducted which would provide a thorough understanding of the networks, allowing for an assessment of cultural significance, an awareness of issues that might affect that significance, and the formulation of policies for retention. Extensive desk-based study, archival research, and fieldwork was carried out at the Woodstock gas works, the Cape Town grain elevator, and the surviving country grain elevators that comprise the respective networks. Both the key sites were recorded during their final days of operation, with a detailed site inventory being created for the Cape Town grain elevator, together with an inventory of sites for the country elevators. It was found that the attitude to industrial heritage is changing rapidly, but that it is heavily influenced by aesthetic and economic considerations. The Woodstock gas works was demolished, and the site cleared, with very little active consideration being given to its conservation. By way of contrast, the Cape Town grain elevator, now derelict, has been the subject of a draft Conservation Plan, albeit one prepared without public participation. The process has stalled as the developer attempts to reconcile aesthetic and economic drivers with a publicly held commitment to the conservation, and marketing, of 'heritage'. The thesis concludes by proposing a new approach to dealing with networked industrial landscapes. It suggests that the surviving country elevators can not only be put to good use for the purpose of sustainable development in terms of Agenda 21, but that the network which historically links them to the Cape Town elevator could itself be re-established in the cause of social transformation.